Project Based Learning and Student Academic Achievement: Cumulative Evidence from Meta-Analysis - Jamila (JSE, 2024)
Project based learning is a more essential mode to enhance students’ achievement in educational practices. Focus of this review is Project[1]Based Learning but not the various “close approaches” such as inquiry[1]based learning and problem based. This meta-analysis is done for finding how the project-based learning approach impacts the academic achievement of students. Literature related to the research question was searched from various databases covering studies published between 2000 and 2023. Codification is an important step; therefore, all the studies carefully selected for meta-analysis were coded. The study’s eight research looked at how project-based learning benefited students’ academic performance. The Effect size for each study was obtained by using Cohen’s d value. Analysis shows that the project-based learning strategy outperforms as compared to traditional approaches in terms of helping pupils in a variety of areas. The size of the effect was between 0.13 to 3.70. Interval of confidence has been discovered 1.217(95 % Cl, SE= 0.379) concerning the achievement of the students with a variety of standards. It is investigated that all existing literature included indicates that learning through projects has a positive influence on achievement. Transitional variables dissection has been done at meta-analysis studies, distinct areas, academic tier, number of included participants, total time, and varieties of publications. Among these studies, three exhibited a large effect size, one a medium, three showed a small effect size, and one study showed a very small effect size. Among these studies, the largest effect size is observed at the elementary level. The study highlighted the positive effect of project base learning and can be used as an effective strategy for improving the educational achievement of learners in different subjects as compared to conventional teaching methods.